Hypolipidemic and Hepatoprotective Effects of High-Polydextrose Snack Food on Swiss Albino Mice - Jin Han Yang; Thi Thu Tra Tran; Van Viet Man Le (Journal of Nutrition and Metabolism)
In this study, the hepatoprotective and hypolipidemic effects of high-polydextrose snack food on Swiss albino mice were investigated. The mice were randomly divided into three groups: control diet, high-fat diet, and high-fat and fiber diet groups. Addition of high-polydextrose snack to the high-fat diet resulted in significant reduction in the liver weight, the accumulation of lipid droplets in liver, and the liver damage of hyperlipidemic mice in comparison with the high-fat diet. The high-polydextrose snack also decreased the content of total triglyceride, cholesterol, and low-density lipoprotein cholesterol as well as the alanine aminotransferase and aspartate aminotransferase activities in the mice serum. In addition, the high-polydextrose snack significantly increased the high-density lipoprotein cholesterol content of the hyperlipidemic mice. Consequently, use of high-polydextrose snack generated hepatoprotective and hypolipidemic effects on hyperlipidemic mice.